Men, war, and logics of practicality: the interlinkage between gender constructions and individual violence - Quest, Hendrik (Interconnecting the violences of men, 2025)
This chapter foregrounds an understanding of post-conflict male violence as enactments of context-specific, constructed logics of practicality, a learned, often subconscious knowledge of what behaviour is expedient under specific circumstances. Building on practice-theoretical ideas, the chapter refers to constructed social antagonisms, in particular those between men and women, perpetrators and victims of violence, as well as fighters and civilians, to make sense of different forms of male violence. I argue that gender constructions revolving around these antagonisms create logics of practicality conveying to individuals that the perpetration of violence is a feasible means to, among others, prove one’s masculinity or further the subordination of women, civilians, or feminised others. The chapter first conceptualises the three antagonisms named above as foundation for conflict-related violence-centred masculinities. Using interview material gathered in Liberia, the chapter then offers examples for individual logics of practicality and how they link to wider, violence-centred gender constructions. It becomes clear that while logics of practicality are individual in nature, the way they are informed by and interlink with the three identified antagonisms is more general across individual life histories. In the conclusion, I ponder the question of how such logics of practicality can change.